Ceramic evidence in the fish-salting Workshop 23 at Troia (Portugal): amphorae and pitchers - Vaz Pinto, Inês; Patrícia Magalhães, Ana; Brum, Patrícia; Araújo dos Santos, Filipa (Rei Cretariae Romanae Fautorum Acta, 2022)
In 2016, a rescue excavation took place in the Workshop 23 in the large fish-salting production centre of Troia, on the shoreline of the Sado River estuary, that is suffering a severe erosion process mainly caused by tidal currents. The archaeological campaign exposed the contexts of three vats, two of them still preserving fish remains from the last production. One is the first in Troia to reveal a predominance of mackerel. The ceramic evidence attending Vat 9, with its preponderance of the Dressel 14, Variant C amphora in association with pitchers, revealed 'industrial' refuse of the second half of the 2nd century. This find brings additional evidence for the end of the first phase of production in Tróia, reflecting the weight of the regional pottery production, along with some imports from other provinces due to trade contacts.